A species-specific individual-based simulation model of mixed mangrove forest stands - Estacio, Ian (Archīum Ateneo, 2019)
A species-specific spatially explicit individual-based model has been developed to simulate the development of mixed mangrove forest stands featuring eight species. The model is a forest stand model that forecasts mangrove forest development in a 50 m x 50 m plot by simulating the recruitment, growth, and mortality of individual mangrove trees. Species-specific growth rates, shade responses, and salinity responses of each species were incorporated to observe differences in forest structure given different salinity conditions. The model used a modified Field of Neighborhood (FON) approach that considers species-specific responses to shading and a salinity response function that considers the species-specific salinity upper boundary value of optimum growth and maximum porewater salinity of a mangrove. Simulation results of 300 years given salinity conditions in a specific site in Katunggan It Ibajay (KII) showed matching dominant species in the site. Simulation results of 500 years given extreme low and high salinity values showed consistent forest dynamics where above-ground biomass and tree count approach certain limit values as the forest stand matures. Simulation results also of 300 years given salinity values ranging from 1 – 37 ppt showed the different dominant species for different salinity conditions.